Pemodelan Deteksi Dini Krisis Mata Uang Berdasarkan Indiktor Nilai Tukar Nominal - Adebun Adebun; Sugiyanto Sugiyanto; Isnandar Slamet (Institut Ilmu Sosial dan Manajemen STIAMI, 2019)
The financial crisis by definition is a situation where several financial assets lose most of their nominal value. The financial crisis experienced by Indonesia in 1997 had a severe impact on the Indonesian economy, so a model was needed to detect this crisis. The financial crisis can be detected using the nominal exchange rate indicator. This study aims to determine the appropriate combination of volatility models and the Markov switching model as a model for detecting financial crises in Indonesia based on nominal exchange rate indicators. The nominal exchange rate indicator taken from 1990 to 2018 is used to build a model for early detection of the financial crisis in Indonesia. The results showed that the combined exponential generalized autoregressive conditional heteroscedasticity and Markov regime switching, MRS-EGARCH (3,1,1) volatility models were both used to detect financial crises in Indonesia based on nominal exchange rate indicators